Futuro del TPP ante el retiro de EE.UU. - Posada, Carlos (2017)
The purpose of this article is to analyze the background of the negotiation and signing of an ambitious Multilateral Trade Agreement – TPP, whose purpose was to establish a commercial zone between Southeast Asian countries and countries of the Americas, which together represent approximately 40% of the world economy with a population of around 800 million people. This effort, which began with the negotiation of P4, was later expanded with the inclusion of the United States of America and other countries that joined the process. Among the issues covered by this Agreement, there are some that cause rejection by some sectors, due to the implications for their economy. However, because of the position declared by the current President of the United States, Donald Trump, this process to reach a comprehensive and ambitious Agreement has stopped, and after that, several members have also expressed their intention to withdraw the process too. In the following months we will see the effects of those decisions.